2019
DOI: 10.1177/1729881419853981
|View full text |Cite
|
Sign up to set email alerts
|

Position/force control of master–slave antagonistic joint actuated by water hydraulic artificial muscles

Abstract: Because of the high force-weight ratio of water hydraulic artificial muscle and its high compatibility with an underwater environment, the water hydraulic artificial muscle has received increasing attention due to its potential uses in marine engineering applications. The master-slave anthropopathic joint actuated by water hydraulic artificial muscles is light and small, and it has good maneuverability for underwater manipulators. However, the control methodologies for water hydraulic artificial muscle joint h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Moreover, the difference of model ratio between actuator 2 and actuator 3 declines with contraction ratio increases, at the same operating pressure. From equations ( 10), (11), and ( 14), the curves are shown in Figure 11. With the wall thickness of rubber tube increases, the contraction force declines under a certain contraction scope (0�e � 0.22).…”
Section: Wall Thickness Model Of the Rubber Tubementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the difference of model ratio between actuator 2 and actuator 3 declines with contraction ratio increases, at the same operating pressure. From equations ( 10), (11), and ( 14), the curves are shown in Figure 11. With the wall thickness of rubber tube increases, the contraction force declines under a certain contraction scope (0�e � 0.22).…”
Section: Wall Thickness Model Of the Rubber Tubementioning
confidence: 99%
“…And the maximum contraction force is approximately 12 kN when the operating pressure is 6 MPa. A novel high-strength WHAM that can export 15 kN at 6 MPa with 30 mm diameter was developed by Dayong et al 11 Mori et al 12,13 developed a WHAM with an external diameter of 40 mm and a total length of 700 mm. The maximum contraction force can reach 28 kN when the operating pressure is 4 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial muscle has made significant progress in structures and materials, 17,18 actuation, 19,20 modeling analysis, 21 and sensor control. 22,23 However, the long-term service capability is also crucial. 24 Currently, the fatigue research of artificial muscles mainly focuses on pneumatic artificial muscles (PAMs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, to carry more than 20 kN of tension, the diameter of the wire rope must be at least 6 mm. The water hydraulic artificial muscle developed by Zhang et al 4 and Ning et al 5 can output a force of more than 20 kN, but uses a rope with a diameter of 8 mm on the joint. Experimental results have revealed that the actual joint rotation angle will be smaller than the theoretical value owing to the excessive rigidity of wire rope.…”
mentioning
confidence: 99%